Genetic differentiation within multiple common grassland plants supports seed transfer zones for ecological restoration. Issue 1 (31st March 2016) - Durka, Walter; Michalski, Stefan G.; Berendzen, Kenneth W.; Bossdorf, Oliver; Bucharova, Anna; Hermann, Julia‐Maria; Hölzel, Norbert; Kollmann, Johannes
Summary: Ecological restoration of grasslands is increasingly based on regional seeds derived from predefined seed transfer zones. However, the degree and spatial pattern of genetic differentiation among provenances of different seed transfer zones is largely unknown. We assessed the genetic differentiation among eight out of 22 German seed transfer zones for seven common grassland species ( Arrhenatherum elatius, Centaurea jacea, Daucus carota, Galium album, Hypochaeris radicata, Knautia arvensis and Lychnis flos‐cuculi ) using AFLP markers. We analysed genetic population structure with AMOVA and Bayesian cluster analysis and tested for isolation by distance and isolation by environment. In all of the investigated species, almost all pairs of provenances were genetically differentiated. Bayesian cluster analysis revealed species‐specific numbers and spatial patterns of gene pools, with between two ( Arrhenatherum ) and eight clusters ( Lychnis ). Most investigated seed transfer zones represented a unique gene pool in the majority of the species. We found isolation by distance in four species, isolation by environment, driven by climatic seasonality, in three species, and a lack of both in three species. Thus, the observed genetic differentiation appears to be caused by both neutral and adaptive processes. Synthesis and applications . Our study shows that grassland plants are indeed strongly genetically differentiated across Germany supporting the strategy of seed transfer zones for ecological restoration. Although the predefined seed transfer zones are unlikely to match the exact genetic structure of many species, they serve their purpose by capturing a substantial amount of intraspecific genetic variation across species.